'Man up!' bullying and resilience within a neoliberal framework. (25th November 2016) - Sims-Schouten, Wendy; Edwards, Simon
ABSTRACT: This study investigates perceptions in relation to bullying, with a particular focus on discussions around resilience, drawing on data from focus group interviews with young people (mean age 14 years old), parents and teachers ( N  = 40). We view self-conduct and the governance of human behaviour as situated within a neoliberal framework, locating accountability and responsibility within the individual. Our methodological framework consists of a multi-level 'synthesised' discourse analysis. Firstly, drawing on discursive psychology, we focus on the interactive accomplishments of talk, such as managing facts, blame and accountability. The second level of discourse analysis focuses on the wider discourses that participants draw on to make sense of themselves, including common sense discourses and ideologies. In their narratives, the participants construct resilience in relation to bullying in terms of individual empowerment, responsibility and 'manning up'; a skill that can be taught and acquired. Not only that, long-term implications of bullying are negated in favour of a neoliberal approach towards self-responsibility in the here and now. This has implications for strategies in relation to bullying and supporting young people in building resilience. More research is needed to establish key notions in relation to resilience, and the multidimensionality of protective factors in relation to bullying.